A Bibliometric and Visualized Analysis of Cardiac Regeneration Over a 20-Year Period - Ma, Siyuan; Yan, Junyu; Chen, Lu; Zhu, Yingqi; Chen, Kaitong; Zheng, Cankun; Shen, Mengjia; Liao, Yulin (Frontiers in Cardiovascular Medicine, 2021)
Background: Recent researches have suggested that cardiac regeneration may have widely applicable potential of treating heart failure. A comprehensive understanding of the development status of this field is conducive to its development. However, no bibliometric analysis has summarized this field properly. We aimed to analyze cardiac regeneration-related literature over a 20-year period and provide valuable insights. Methods: Publications were collected from the Web of Science Core Collection. Microsoft Excel, VOSviewer, CiteSpace, and alluvial generator were used to analyze and present the data. Results: The collected 11700 publications showed an annually increasing trend. The USA and Harvard University were the leading force among all the countries and institutions. The majority of papers were published in Circulation Research and Circulation was co-cited the most. According to co-citation analysis, burst detection and alluvial flow map, cardiomyocyte proliferation, stem cells including first-and second-generation, extracellular vesicles especially exosomes, direct cardiac reprogramming, macrophages, microRNAs and inflammation have become more and more popular recently. Conclusions: Cardiac regeneration remains a research hotspot, and develops rapidly. How to modify cardiac regeneration endogenously and exogenously may still be the hotspot in the future and should be discussed more deeply.